2016
DOI: 10.1016/j.jconrel.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Sonoporation enhances liposome accumulation and penetration in tumors with low EPR

Abstract: The Enhanced Permeability and Retention (EPR) effect is a highly variable phenomenon. To enhance EPR-mediated passive drug targeting to tumors, several different pharmacological and physical strategies have been evaluated over the years, including e.g. TNFα-treatment, vascular normalization, hyperthermia and radiotherapy. Here, we systematically investigated the impact of sonoporation, i.e. the combination of ultrasound (US) and microbubbles (MB), on the tumor accumulation and penetration of liposomes. Two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 54 publications
2
113
0
1
Order By: Relevance
“…As a drug delivery system, liposomes consist of an aqueous center for incorporation of hydrophilic molecules and exhibit some advantages including biocompatibility, capacity for self‐assembly, ability to carry large drug payloads (Sercombe et al, ). Consistent with our findings, liposomes as carrier for antitumor agent show accumulation at tumor site at high levels (Kang et al, ; Theek et al, ). Intriguingly, lungs showed significant uptake for free HMME but did not trap liposomes inside, indicating the low side effects of liposomal HMME for SDT.…”
Section: Discussionsupporting
confidence: 92%
“…As a drug delivery system, liposomes consist of an aqueous center for incorporation of hydrophilic molecules and exhibit some advantages including biocompatibility, capacity for self‐assembly, ability to carry large drug payloads (Sercombe et al, ). Consistent with our findings, liposomes as carrier for antitumor agent show accumulation at tumor site at high levels (Kang et al, ; Theek et al, ). Intriguingly, lungs showed significant uptake for free HMME but did not trap liposomes inside, indicating the low side effects of liposomal HMME for SDT.…”
Section: Discussionsupporting
confidence: 92%
“…5). Recently, Deese et al reported that sonoporation using MBs enhanced the extravasation and penetration of relatively large liposomal nanocarriers out of the blood vessels into the tumor interstitium by a variety of mechanisms, including perfusion modulation, mechanical disruption, and pore formation in tumor vessels [30]. Whether a similar mechanisms drive drug delivery and uptake in presence in presence of nanobubbles is currently not known.…”
Section: Discussionmentioning
confidence: 99%
“…Sonoporation, the temporary formation of pores in the cell membrane by a combination of MB and US or focused US (FUS), has been shown to enhance drug delivery . MB can be modified for this purpose, e.g., by loading them with drugs or therapeutic DNA, binding targeting ligands onto their surface, or refining their size, shell thickness, and circulation time .…”
Section: Promising Directions For Ca Developmentmentioning
confidence: 99%